Cross-Sector Partnerships: Factors Supporting Social Innovation by Nonprofits. Issue 3 (26th May 2016) - Shier, Micheal L.; Handy, Femida
ABSTRACT: This research investigated key aspects of cross-sector partnerships that support the socially innovative efforts of direct-social-service nonprofit organizations (DSSNs). Utilizing qualitative research methods, executive directors of DSSNs in Alberta, Canada, were interviewed. Findings highlight four general analytic categories for cross-sector partnerships: (1) structure of engagement; (2) alignment between partnering organizations; (3) clarity of outcomes; and (4) interpersonal dynamics among partnership actors. The findings provide a conceptual model of the conditions that support successful cross-sector partnerships for further empirical testing. A greater emphasis among public policy actors to create these conditions for successful cross-sector partnerships is recommended.